Desarrollo del lenguaje infantil y la lectoescritura - Marcalla Andrango, María Alexandra (2016)
It investigates the development of language and literacy in children of "República de Colombia" School, since it has witnessed the difficulty in pronunciation of language, and therefore this affects the child writing in the future. They have no interest in listening to stories, was not perfmed exercises in the classroom there was little stimulation to develop language skills. The aim of the research was to determine whether the development of language influences in literacy, pictograms, stories, nursery rhymes, and oral exercises can apply the teacher in and outside the classroom because through these recreational activities playful skills language playful in children by creating situations. The methodology used in the project is qualitative and quantitative because it is realistic, explicit rules, and statistics was done which allow us to deduce data obtained from the research was conducted. It has an impact of social action showing a lot of children with problems in the development of their language being a problem that can solve long or short term. The language is very essential in the development of children both at school and social environment so that they can manage in the future, the child's language is increased as grows, but some children have not achieved by low income will not able to receive adequate stimulation for language development. One way of solution to the problem is to provide adequate stimulation for children to develop their language to develop within the educational and social environment by publicizing how to express their ideas, thoughts, and feelings through language.